Tourism Potential Of Sport Hiking In Ciharus Lake Kamojang Bandung District - Moch. Ridwan Mahesa; Respaty Mulyanto; Rizal Ahmad Fauzi (UNIVERSITAS NEGERI MAKASSAR, 2024)
The potential for hiking sports tourism in Lake Ciharus Kamojang is not potential to do, because not all tourist attractions in Kamojang can be visited like Lake Ciharus. Because this ciharus lake is a nature conservation protected forest area and is included in the category of nature reserve areas which have characteristics in the form of diversity and unity of types of living things, in the form of animals, plants, and their ecosystems. Because the government prefers to make it conservation to maintain and protect the high biodiversity in Lake Charles. Conservation areas, indeed, have great potential for the economy, but it must be underlined that the Lake Ciharus conservation area is not only an economic interest to be raised but there must be ecological value. However, for the time being, Lake Ciharus is still under review by BKSDA. The research method used is a qualitative method with a descriptive research design in the form of interviews, observation and documentation.